Analisis Pengaruh Sisa Lebih Perhitungan Anggaran (SILPA) Pada Belanja Modal Yang Dilakukan Pada Kota Surabaya - Ardana, Ericho Rizal; Husada, Aldiansyah Dwi Putra; Subakti, Annas (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
The study on the influence of Budget Calculation Surplus (SiLPA) on capital expenditure in the city of Surabaya aims to determine the influence on the components in the APBD in the form of Budget Calculation Surplus (SiLPA) and its constituent elements. The sample used in this study is the city of Surabaya. In this research process, a research method was used in the form of a literature study comparing journals from previous studies that were relevant to the condition of the Surabaya city government’s financial notes. Based on the results of the analysis that the author has conducted, it shows that one of the components of the APBD (SILPA) is significantly influenced by its constituent elements. Namely the most important capital expenditure, non-capital expenditure and excess income have a significant effect on the Budget Calculation Surplus (SiLPA).